Cover Image, Volume 70, Issue 3. Issue 3 (5th January 2022) - Lange, Jenny; Gillham, Olivia; Alkharji, Reem; Eaton, Simon; Ferrari, Giulia; Madej, Monika; Flower, Michael; Tedesco, Francesco Saverio; Muntoni, Francesco; Ferretti, Patrizia
Abstract : Cover Illustration: Dystrophin, a protein mutated in Duchenne muscular dystrophy, is expressed in human astrocytes differentiated from neural stem cells and grown tri‐dimensionally (3‐D) in a hydrogel. Growing astrocytes in 3D appears to greatly increase dystrophin immunostaining as compared to 2D culture. (See Ferritti, P. et al, https://doi.org/10.1002/glia.24116 .)